Uganda : 2013 Article IV Consultation and Sixth Review Under the Policy Support Instrument, Request for a Three-Year Policy Support Instrument and Cancellation of Current Policy Support Instrument-Staff Report;Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2013)
This paper focuses on Uganda's 2013 Article IV Consultation and Sixth Review Under the Policy Support Instrument, Request for a Three-Year Policy Support Instrument and cancellation of Current Policy Support Instrument. Driven mainly by investment and trade, growth has recovered to about 5 percent, a stronger than expected rebound from the low 3 1\2 percent expansion registered last year. Fast implementation of road construction, the start of operations of the Bujagali hydropower plant, and a good harvest boosted aggregate demand. Envisaged public finance management reforms are set to address the problems of persistent under budgeting, arrears accumulation, and failure to sanction financial irregularities.